IDENTIFICATION OF LAND USE CHANGES USING THE OBJECT BASED IMAGE ANALYSIS (OBIA) METHOD IN BUNGUS TELUK KABUNG DISTRICT - Wahyuni, Sri Agustia; Fitriawan, Dedy; Triyatno, Triyatno; Arif, Dian Adhetya (Remote Sensing Technology Study Program, 2023)
Object-based image analysis (OBIA) is an image classification that considers not only the spectral aspects of objects, but also their spatial aspects. This classification is guided by objects that have distribution patterns from object samples which are used as references for their accuracy. However, this object-based classification process must be taken into account when looking at color and calculating it so that there is no error in classification. In this research, the OBIA method was used to identify changes in land use in the Bungus Teluk Kabung District in 2012, 2017 and 2022. By using the OBIA method, identification results were obtained in areas where land use changes occurred between 2012 and 2017, which were identified as having changed from open land to built-up land. with an area of 355.84ha, plantations 22.62ha and rice fields 20.97ha. From 2017 to 2022, it was identified that there was a change in land use from dry land forests to 6.30ha of built-up land. The change in open land to built-up land was 7.47ha. Plantations experienced changes to 6.21ha of built-up land and 9.27ha of rice fields. Meanwhile, bushes/shrubs experienced changes in plantations of 2.47ha.